Fanconi's aplastic anaemia with short stature. Absence of response to human growth hormone. Issue 4 (April 1975) - Gleadhill, V; Bridges, J M; Hadden, D R
Abstract : A patient with idiopathic marrow hypoplasia associated with short stature and other anomalies (Fanconi's anaemia) is described: treatment with human growth hormone for one year did not accelerate his growth rate or significantly affect his anaemia: androgen treatment considerably improved both features. Endocrine studies suggest that though he had poor and insufficient production of endogenous growth hormone to insulin-induced hypoglycaemia, the major defect in this syndrome is determined more at the end-organ than at the pituitary or gonadal level.